2017
DOI: 10.3390/su9060921
|View full text |Cite
|
Sign up to set email alerts
|

Research on Customer Satisfaction in Marine Cultural and Sustainable Tourism—A Case Study of Shanghai

Abstract: Abstract:In recent years, marine cultural tourism, an emerging tourism mode, has become more and more popular among tourists, and demonstrates broad market prospects. However, Chinese marine cultural tourism is still in the development and growth stage, and the level of customer satisfaction is uneven. The improvement of the customer satisfaction level is conducive to meeting customers' demands in marine cultural tourism and enhancing the competitiveness of Chinese marine cultural tourism. Based on theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Ross (2013) analyzed the influence of competitiveness on visitor satisfaction using visitor survey results from a metropolitan zoo [40]. Using Shanghai as a case study, Zheng et al (2017) concluded that improving customer satisfaction is conducive to meeting customers' demands and enhancing the competitiveness in marine culture tourism [54]. He et al (2017) proposed that improving tourists' satisfaction is crucial for ensuring destination competitiveness in the market [55].…”
Section: Satisfaction-destination Competitivenessmentioning
confidence: 99%
“…Ross (2013) analyzed the influence of competitiveness on visitor satisfaction using visitor survey results from a metropolitan zoo [40]. Using Shanghai as a case study, Zheng et al (2017) concluded that improving customer satisfaction is conducive to meeting customers' demands and enhancing the competitiveness in marine culture tourism [54]. He et al (2017) proposed that improving tourists' satisfaction is crucial for ensuring destination competitiveness in the market [55].…”
Section: Satisfaction-destination Competitivenessmentioning
confidence: 99%
“…In regard to customer satisfaction, Cardozo applied the concept of satisfaction to the field of marketing for the first time in 1965 [37]. Customer satisfaction was conducive to promoting customers' consumption behaviors [38].…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…Product safety and environmental impact have also become important criteria. The improvement of the customer satisfaction level is conducive to meeting customers' demands (Zheng et al, 2017). Accountability to customers in this area can be expanded in providing good service at a fair price, in handling complaints, in undertaking the communication with the customer, etc.…”
Section: Rezultati I Raspravamentioning
confidence: 99%